2017
DOI: 10.1002/2016ms000702
|View full text |Cite
|
Sign up to set email alerts
|

Using precipitation, vertical root distribution, and satellite‐retrieved vegetation information to parameterize water stress in a Penman‐Monteith approach to evapotranspiration modeling under Mediterranean climate

Abstract: Recent studies have shown that global Penman‐Monteith equation based (PM‐based) models poorly simulate water stress when estimating evapotranspiration (ET) in areas having a Mediterranean climate (AMC). In this study, we propose a novel approach using precipitation, vertical root distribution (VRD), and satellite‐retrieved vegetation information to simulate water stress in a PM‐based model (RS‐WBPM) to address this issue. A multilayer water balance module is employed to simulate the soil water stress factor (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 99 publications
0
26
0
Order By: Relevance
“…Which is central to our method is using microwave EDVI to quantify the stomatal and canopy resistance under both clear sky and cloudy sky. Most of previous resistance-based LE methods are based on optic VIs [17][18][19] which cannot be effectively implemented under cloudy sky. Their validations are thus limited to under clear or partly cloudy sky.…”
Section: Summary Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Which is central to our method is using microwave EDVI to quantify the stomatal and canopy resistance under both clear sky and cloudy sky. Most of previous resistance-based LE methods are based on optic VIs [17][18][19] which cannot be effectively implemented under cloudy sky. Their validations are thus limited to under clear or partly cloudy sky.…”
Section: Summary Of the Methodsmentioning
confidence: 99%
“…VIs are typically used for the estimation of canopy resistance (or conductance) in the PM model [8]. Previous studies have shown that optical VI-based resistance and LE estimation show good performances at the 8-day or 16-day time scale and under clear or less cloudy sky conditions [11,[17][18][19]. However, since the optical VIs are retrieved based on the visible, near-infrared and shortwave-infrared bands [19] which are very sensitive to clouds and aerosols, their applicability under cloudy and overcast skies is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We present an implementation of the model that calculates the rooting zone storage for both the overstory and understory. Then, we compare estimates of S r obtained with this parameterization against S r values obtained by calibrating a local water balance model against observations of latent heat flux and soil water content at 15 eddy covariance sites of the FLUXNET network (re3data.org, 2018; Baldocchi et al, 2001). We assess the effect of using optimality-based S r estimates on the performance of the local water balance model during validation.…”
Section: Introductionmentioning
confidence: 99%
“…are representative for the actual site conditions, at least at the temperate and boreal sites. Under Mediterranean conditions, transpiration may be more sensitive to the vertical 20 distribution of soil moisture and roots (Bai et al, 2017). Therefore, the use of a bulk !…”
Section: Parameterizationmentioning
confidence: 99%